Pengaruh Layanan Bimbingan Kelompok dengan Teknik Sosiodrama Terhadap Perilaku Asertif Siswa - Dewi, Karlina (Indonesian Journal of Guidance and Counseling: Theory and Application, 2017)
The purpose of this study to describe assertive behavior of students before and after being given the group counseling with sociodrama techniques and whether group counseling with sociodrama techniques can improve student assertive behavior. This study includes into experimental research design with one group pretest-posttest design. Pretest and posttest in the form of assertive behavior scale. Samples were ten students of class IX with purposive random sampling technique sampling. Hypothesis testing using Wilcoxon test by comparing the smallest level of pre and posttest results, obtained results Tcount 0 < Ttable = 8, which means Ha accepted and Ho rejected. Results of this study are (1) the level of assertive behavior of students being with an average percentage of 40%. (2) 10 students has increased assertive behavior with an average percentage of 72%. Therefore, guidance and counseling teachers at school can use group counseling with sociodrama techniques to improve student assertive behavior.